Face-to-Face Instruction and Blended Learning Related to Students’ Commitment in Science Courses - Lavenia, Jovita; Tiarani, Vinta (Indonesian Journal of Educational Research and Review, 2023)
Changes in instructional modes that have occurred can trigger various perceptions and different learning commitments, especially in lectures that are identic to perform hands-on science, such as science courses. This study aims to analyze students’ perceptions of blended learning and face-to-face modes in science courses related to learning commitment after the Covid-19 pandemic. Using phenomenological method, the research was conducted with six students as participants. The data was collected by interview, observation, and documentation techniques. Triangulation was used to validate the data, while a data analysis technique is using Miles and Huberman. The results show that there are differences in students’ perceptions and commitments in science courses with both learning modes. Students tend to perceive face-to-face learning more positively than blended learning because activities perform more interactively. Students’ commitments are better during face-to-face learning than during blended learning. Based on the results, this study concludes that positive perceptions shape better learning commitments than negative perceptions.